PENGARUH LITERASI KEUANGAN, MODERNITAS INDIVIDU, UANG SAKU DAN KONTROL DIRI TERHADAP PERILAKU KONSUMTIF MAHASISWA PRODI S1 PENDIDIKAN EKONOMI ANGKATAN TAHUN 2016 FAKULTAS EKONOMI UNIVERSITAS NEGERI MALANG - Dewi Kumalasari; Yohanes Hadi Soesilo (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2019)
Consumptive behavior of Indonesian society contributes to the depreciation of the rupiah against the US dollar, especially the consumption of imported products. The amount of consumption of such imports helped push the current account deficit widened to 3 percent of GDP in the second quarter of 2018. People especially students who like to follow the trend of electronics, and import or non-import spending will tend to behave consumptive. Consumptive behavior does not occur alone, but happen because of financial literacy, modernity individuals, allowance and self-control to consume. The phenomenon occurs at the Faculty of Economics, State University of Malang shows students follow the trend of clothes, handphone with high prices. This behavior will lead to student consumptive life. This study uses a quantitative research approaches. The population of this study are 163 students of Economic Education Program, Department of Economic Development, Faculty of Economics, State University of Malang. The technique used in this research is proportional random sampling technique and obtained 116 respondents. The analytical method used is multiple linear regression analysis using a questionnaire. The results of this research showed five results. First, financial literacy negatively affected on consumptive behavior with effective contribution by 9,22%. Second, modernity individuals positively affected on consumptive behavior with effective contribution by 8,23%. Third, allowance positively affected on consumptive behavior with effective contribution by 35,03%. Fourth, self-control negatively affected consumer behavior with effective contribution by 17,54%. Fifth, financial literacy, modernity individuals, allowance and self-control positively affected on consumptive behavior with effective contribution by 70,00%.